Sequential limit analysis for clamped circular membranes involving large deformation subjected to pressure load. (May 2019) - Zhang, Chenghu; Fan, Lijia; Tan, Yufei
Highlight: Extend sequential limit analysis to clamped circular membrane with large deformation. Moving coordinate systems are adopted to deal with plane stress direction change. Velocity field assumption and geometry update strategy of cause little error. Yield level and bending moment are main influencing factor of limit load estimation. Relative error can be controlled within 17% even for extreme material parameters. Abstract: In this study, we investigate the extended sequential limit analysis for clamped circular membranes involving large deformation subjected to pressure load. Moving coordinate systems were adopted, and a shape and geometry update strategy was proposed to deal with the consideration of plane stress direction change. A sequence of optimization problems formulated on the upper-bound theorem was solved to perform the nonlinear cumulative sequence of load-deflection curves. In the formulation, the rigid-perfectly-plastic behavior were used. Then, some numerical simulations by ABAQUS were conducted to assess the parameters and simplification effect on the sequential upper-bound formulation derived. The results show that the sequential limit analysis gives a good estimation of the plastic limit load and load-deflection behavior. The collapse mechanism assumption and the update strategy of shape and geometry cause little error. Meanwhile, the limit state yield level and bending moment are the main factors that cause the relative error of limit load estimation to decrease as the elastic modulus, yield strength, and thickness increase and the radius decreases. Synthetically, the sequential limit analysis allow a wide range of thickness-radius ratios, especially for low-elastic-modulus materials, and the relative errors can be controlled within 17%, even for materials with extreme parameters.